Suppression of Hypertrophy During in vitro Chondrogenesis of Cocultures of Human Mesenchymal Stem Cells and Nasal Chondrocytes Correlates With Lack of in vivo Calcification and Vascular Invasion - Anderson-Baron, Matthew; Liang, Yan; Kunze, Melanie; Mulet-Sierra, Aillette; Osswald, Martin; Ansari, Khalid; Seikaly, Hadi; Adesida, Adetola B. (Frontiers in Bioengineering and Biotechnology, 2021)
Objective: Human nasal septal chondrocytes (NC) are a promising minimally invasive derivable chondrogenic cell source for cartilage repair. However, the quality of NC-derived cartilage is variable between donors. Coculture of NC with mesenchymal stem cells (MSCs) mitigates the variability but with undesirable markers of chondrocyte hypertrophy, such as type X collagen, and the formation of unstable calcifying cartilage at ectopic sites. In contrast, pure NC forms non-calcifying stable cartilage. Formation of a stable NC-MSC coculture cartilage is crucial for clinical application. The aim of this study was to explore the utility of parathyroid hormone-related peptide hormone (PTHrP) to suppress chondrocyte hypertrophy in NC-MSC cocultures and form stable non-calcifying cartilage at ectopic sites. Methods: Human NC and bone marrow MSCs, and cocultures of NC and MSC (1:3 ratio) were aggregated in pellet form and subjected to in vitro chondrogenesis for 3 weeks in chondrogenic medium in the presence and absence of PTHrP. Following in vitro chondrogenesis, the resulting pellets were implanted in immunodeficient athymic nude mice for 3 weeks. Results: Coculture of NC and MSC resulted in synergistic cartilage matrix production. PTHrP suppressed the expression of hypertrophy marker, type X collagen (COL10A1), in a dose-dependent fashion without affecting the synergism in cartilage matrix synthesis, and in vivo calcification was eradicated with PTHrP. In contrast, cocultured control pellets without PTHrP treatment expressed COL10A1, calcified and became vascularized in vivo.